If $ax^2-bx+c=0$ roots are $\alpha, \beta $ then find the roots of $$acx^2-b(c+a)x+(c+a)^2=0$$ from $\alpha, \beta$.

I need to find the best way to anwser this question

my answer

Say $\gamma, \delta $ are the roots of given equation then $$\gamma\cdot\delta=\frac{(c+a)^2}{ac}=(\alpha+1/\beta)(\beta+1/\alpha)$$ and $$\gamma+\delta=\frac{b(c+a)}{ac}=(\alpha+1/\beta)+(\beta+1/\alpha).$$ So roots are $$(\alpha+1/\beta),(\beta+1/\alpha)$$ this method is less powerful (it is hard to find the relation of $\alpha,\beta$ and $\gamma, \delta$)

Can anyone give me a different answer to this question? Thanks!!


Your approach is just fine and also very general. You can also try this method:

Try to form given equation into the old form $ay^2-by+c =0$ and deduce the relation of $x$ and $y$. First divide by $(c+a)^2$:

$$ac(\tfrac{y}{c+a})^2-b (\tfrac{y}{c+a})+1 = 0$$

Now we need a $c$ in place of $1$. So multiply throughout by $c$:

$$a(\tfrac{yc}{c+a})^2-b (\tfrac{yc}{c+a})+c = 0$$

Thus we have found out that $x = \tfrac{yc}{c+a}$ or that $y = x(1+\tfrac{1}{P})$ where $P$ is the product of roots of original quadratic.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.